Analisis Erodibilitas Tanah untuk Budidaya Talas Beneng Berkelanjutan berdasarkan Elevasi - Hanif Maulana; Nuniek Hermita; Andi Apriany Fatmawaty; Dewi Firnia (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Taro Beneng holds significant potential to enhance food security and economic value, particularly in the Banten region. This study aimed to analyze soil erodibility values across Taro Beneng cultivation areas in Talaga Warna, Juhut, and Kaduengang villages to support sustainable land management and optimize crop yields. Conducted in 2024, the research employed a survey method with soil erodibility analysis based on the Wischmeier and Smith (1978) formula, considering parameters such as soil texture, structure, organic matter, and permeability. Thirty soil samples were collected across three elevation zones to capture variability, and the erodibility (K) values were calculated using Microsoft Excel, with spatial mapping conducted via ArcGIS. Results indicate that organic matter content increases with elevation due to climatic factors influencing decomposition rates. Soil texture ranges from sandy clay loam in Talaga Warna and Juhut to loamy sand in Kaduengang, reflecting the geographical diversity of the Mount Karang region. Soil structure varies from granular to coarse, with differing permeability levels contributing to varied erodibility risks. The highest soil erodibility values were recorded in Talaga Warna and Juhut (K = 0.49), indicating high erosion susceptibility, while Kaduengang exhibited the lowest value (K = 0.36), suggesting more stable soil conditions. These findings highlight the spatial variability of soil erosion risks in Taro Beneng fields, offering insights to guide targeted soil conservation practices. By addressing areas with higher erosion risks, this study provides practical recommendations for sustainable land management to support Taro Beneng cultivation and ensure long-term soil health in the region.